2021
DOI: 10.1111/os.12907
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Lumbar Discectomy for Lumbar Disc Herniation Using an Endoscopic Staining: A Technical Note

Abstract: Symptomatic lumbar disc herniation (LDH) is widely treated using percutaneous endoscopic lumbar discectomy (PELD). In the present PELD surgery, performing decompression under endoscope still takes a long time to explore the rupture site of annulus fibrosus, resulting in prolonged operation time and over-invasion of the undegenerated annulus fibrosus. A wide range of intraoperative exploration also induces an iatrogenic injury of the normal annulus fibrosus, even aggravating intervertebral disc degeneration, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The UBE is widely indicated and has good efficacy in the treatment of diseases, such as LDH and epidural peptide swelling (30). The UBE technique was used for a long time because of its many advantages, but it was gradually stopped being used following the rapid development of single-channel operations; however, after improvements and innovations by Korean scholars, it has begun to be re-appreciated and promoted by domestic physicians in recent years (31). Since we started using this technique at the end of 2020, we found that there are still many intraoperative difficulties and shortcomings that require attention and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The UBE is widely indicated and has good efficacy in the treatment of diseases, such as LDH and epidural peptide swelling (30). The UBE technique was used for a long time because of its many advantages, but it was gradually stopped being used following the rapid development of single-channel operations; however, after improvements and innovations by Korean scholars, it has begun to be re-appreciated and promoted by domestic physicians in recent years (31). Since we started using this technique at the end of 2020, we found that there are still many intraoperative difficulties and shortcomings that require attention and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the LDH often seek medical attention for discogenic low back pain or radiating pain, most of which are caused by herniated discs pressing on nerves (1,2). Percutaneous endoscopic lumbar discectomy (PELD) has recently become popular in the treatment of LDH due to the smaller skin incision, light tissue damage, shorter operation time, rapid recovery, and earlier return to work (3)(4)(5). At present, most studies show that the average length of stay of PELD as a traditional model is 2 to 5 days (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%